Effect of Nutrient Element and Leaf Cutting Year on Tea Quality At Unit Perkebunan (UP) Tambi Wonosobo - Indrabayu Indrabayu; Andree Wijaya Setiawan (Asian Journal of Social and Humanities, 2023)
This research was conducted on the tea plant which has the scientific name Camelia Sinesis L at the Tambi Plantation Unit (UP) located in Tambi Village, Kejajar District, Wonosobo Regency. The purpose of this study was to determine the effect of soil nutrients and the year of cut on the quality of tea leaves at UP Tambi. The flow of thought in this research, where after taking soil samples and leaf samples at the Tambi Wonosobo Tea Plantation Unit with the 4th cutting year (2018) and the 2nd cutting year (2021) then proceed with laboratory testing to determine nutrient content soil and substance content of tea leaves to measure the quality of tea plants. The sample for this study was taken using the instant sample method (Grab Sample), where the samples were taken directly from the soil body at a predetermined location with a depth of 20 cm from the soil surface, while the leaf sampling also used the Grab Sample method. The results of this study showed that the Correlation Test found that the content of Polyphenols, Catechins (EGCG), Flavonoids, and Caffein was influenced by soil nutrients pH, C org, N, available P2O5, P2O5, K2O, CaO, Ca, and Mg, meaning that there the effect of soil nutrients on the quality of tea leaves in the Tambi Plantation Unit (UP), Furthermore, there was no effect of the year of cutting on the quality of the tea leaves as shown by the results that in the 4th cutting year (2018) and the 1st cutting year (year 2021)